2021
DOI: 10.1007/s00217-021-03869-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lacto-fermentation and freeze-drying on the quality of beetroot evaluated using machine vision and sensory analysis

Abstract: This study was aimed at evaluating the effect of freeze-drying and lacto-fermentation on the texture parameters of images and sensory attributes of beetroots. The samples were imaged using a flatbed scanner, and textures from images converted to color channels L, a, b, R, G, B, X, Y, Z were computed. The discrimination of raw and processed beetroots was performed using models based on textures selected for each color channel. The sensory quality of processed samples was determined using the attributes related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
1
8
0
1
Order By: Relevance
“…The overall accuracy reached 98.5%. In the available literature, there are reports on the application of image analysis for the quality evaluation of preserved fruit and vegetables, including pickles [19,20] and lacto-fermented beetroot [21,22]. The results of our research confirmed the usefulness of image processing in the evaluation of preserved products.…”
Section: Resultssupporting
confidence: 76%
“…The overall accuracy reached 98.5%. In the available literature, there are reports on the application of image analysis for the quality evaluation of preserved fruit and vegetables, including pickles [19,20] and lacto-fermented beetroot [21,22]. The results of our research confirmed the usefulness of image processing in the evaluation of preserved products.…”
Section: Resultssupporting
confidence: 76%
“…Microtomography analysis of vegetables can show the 3D structure of the entire analyzed sample. Rybak et al [29] observed similar results for microtomography of freeze-dried red bell pepper, Bialik et al [40] for kiwi berry, and Ropelewska et al [30] for beetroot raw and fermented.…”
Section: Structurementioning
confidence: 74%
“…It is a low-temperature dehydration process that involves freezing the product, lowering the pressure, and then removing the ice by sublimation. This process preserves the product with the structure of the raw material [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Freeze-drying is an effective method to preserve beneficial probiotic bacteria in fermented products for a longer time. It allows for the preservation of a large amount of bioactive compounds and the survival of some bacteria [43,44]. After freeze-drying, a decrease in the number of bacteria was observed in all the samples.…”
Section: Microbiologymentioning
confidence: 97%